2009
DOI: 10.1007/s11224-009-9477-1
|View full text |Cite
|
Sign up to set email alerts
|

Conformational flexibility of pyrimidine rings of nucleic acid bases in polar environment: PCM study

Abstract: The results of calculations of molecular structures of nucleic acid bases in polar environment using Polarized Continuum Model of solvent combined with the MP2/cc-pvdz level of ab initio theory demonstrate considerable polarization of thymine, cytosine, and guanine. This phenomenon can be related to considerable contribution of zwitter-ionic resonant forms into total structure of the studied species. It leads to significant increase (about 30%) of frequencies of the out-of-plane pyrimidine ring vibrations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…Similar feature has been observed in the hydration of uracil and others NABs . An increase of the resonant form contribution into total structure leads to a decrease in the conformational flexibility of the heterocyclic ring The water molecules have a slight effect in the planarity of the uracil ring, in general, with differences lower than 7° in their torsional angles. The distribution of the water molecules in the cluster changes significantly the dipole moment value, and it was significantly high in that with 20 water molecules. The atomic charges were also affected with the progress of the hydration, with an increment in the negative charge on the oxygen and sulfur atoms, and a decrement in the negative value on the nitrogen atoms. As it is expected, hydrophobic sites on NABs are not involved (or not at all) in the formation of the first hydration shell.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Similar feature has been observed in the hydration of uracil and others NABs . An increase of the resonant form contribution into total structure leads to a decrease in the conformational flexibility of the heterocyclic ring The water molecules have a slight effect in the planarity of the uracil ring, in general, with differences lower than 7° in their torsional angles. The distribution of the water molecules in the cluster changes significantly the dipole moment value, and it was significantly high in that with 20 water molecules. The atomic charges were also affected with the progress of the hydration, with an increment in the negative charge on the oxygen and sulfur atoms, and a decrement in the negative value on the nitrogen atoms. As it is expected, hydrophobic sites on NABs are not involved (or not at all) in the formation of the first hydration shell.…”
Section: Resultssupporting
confidence: 64%
“…[88] An increase of the resonant form contribution into total structure leads to a decrease in the conformational flexibility of the heterocyclic ring. [89] 4. The water molecules have a slight effect in the planarity of the uracil ring, in general, with differences lower than 7 in their torsional angles.…”
Section: Effect Of the Water Molecules On The Nucleobase Pair With mentioning
confidence: 99%
“…Investigation of structure of hydrated nucleic acid bases indicated (see refs. [52,53] and references therein) that presence of polar environment can lead to significant polarization of molecules even in the case of absence of strong intermolecular interactions. Taking into account formation of stacks and their dimers in the crystal of thioindirubin it is possible to assume that differences in experimental and calculated values of bond lengths are caused by influence of polar environment in the crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier it was demonstrated that the molecular structure of NABs is sensitive to polar environment [51]. Therefore, it is may be expected that the decrease in aromaticity of a NAB is due to polarizing effect of the second nucleic acid involved in the stacking interaction.…”
Section: Delocalization and Aromaticity In Stacked Base Pairsmentioning
confidence: 99%